Same soybean policy, different responses of agricultural systems: Comparing effectiveness of cropping pattern adjusting in state farms and rural household farms of Heilongjiang, China - Xi Chen; Jinwei Dong; Zhichao Li; Li Sun; Chuantao Ren; Guoming Du; Yuanyuan Di; Nanshan You; Xiaoyong Liao (Geography and Sustainability, 2025)
State farms, although a minority in China’s agricultural sector, play a critical role in regions like Heilongjiang, leading national food production. However, how state farms (SFs) and rural household farms (RFs) respond to food policies, especially the 2017 soybean subsidy policy (post-Sino–U.S. trade war) and the 2019 soybean revitalization policy, remains unclear. This study examines changes in cropping patterns on SFs and RFs in Heilongjiang from 2013 to 2022 using annual crop maps. We find that SFs, with larger and more clustered fields, responded more effectively to the soybean policies: soybean acreage recovery (2019–2021) reached 91.51 % of pre-trade war levels for RFs and 98.2 % for SFs; following the revitalization policy, maize-soybean rotations were implemented four times in 62.3 % of SFs and 45.4 % of RFs. These results highlight the influence of global trade and agricultural policies on cropland management, providing critical insights into sustainable practices and food security across different agricultural systems.